Non Agriculture with Settlement Legality in Boyolali Regency Central Java, Indonesia - Ahmad Kurniadi; Isharyanto Isharyanto (Budapest International Research and Critics University, 2020)
This research has been done to identify changes in agricultural land to non-agriculture causing the establishment of illegal settlements. Viewed from the standpoint of nature this research is descriptive research, carried out in order to help in strengthening old theories or within the framework of developing new theories. Research locations are in the Office of the Regional Planning, Research and Development (BP3D) Boyolali Regency and Boyolali Regency Agriculture Office. Data collection was carried out by interview and literature study. Data analysis technique is done by data reduction, data display and conclusion. The results show that agricultural development will occur if land problems over the conversion of agricultural land into settlements are unavoidable or need to find a solution to a problem that is very urgent, this is by studying the impact of the problem and socializing the community over these impacts and their resolution to obtain clarity of land legality the conversion. When land starts to shrink, domestic food needs will decrease because population growth cannot be avoided every year. For this reason, immediate special handling is needed, such as direct counseling for the community. Will be danger of land conversion is carried out continuously. Development of the latest technology is needed to manage the land so that fertility does not decrease quickly so as to reduce land productivity. Another way replacement of agricultural land which is used as an alternative handling of the legality problem of conversion of agricultural land.